Fungal Malignant Otitis Externa with Facial Nerve Palsy: Tissue Biopsy Aids Diagnosis. (5th February 2014) - Walton, Jenny; Coulson, Chris
Abstract : Fungal malignant otitis externa (FMOE) is a serious and potentially life-threatening condition that is challenging to manage. Diagnosis is often delayed due to the low sensitivity of aural swabs and many antifungal drugs have significant side effects. We present a case of FMOE, where formal tissue sampling revealed the diagnosis and the patient was successfully treated with voriconazole, in addition to an up to date review of the current literature. We would recommend tissue biopsy of the external auditory canal in all patients with suspected FMOE in addition to routine microbiology swabs.